Implementasi Pendukung Keputusan Dalam Pemilihan Calon Peserta Cerdas Cermat Tingkat SMA Menerapkan Metode VIKOR - Nidia Sutrikanti; Hotmelinsa Situmorang; Fachrurrazi Fachrurrazi; Heri Nurdiyanto; Mesran Mesran (STMIK Budi Darma, 2018)
Improving the quality of human resources that can be done with intelligent organizing carefully at the level of Senior High School. In order for the participant to follow intelligently, every participant should not only have the achievement and general knowledge but also must have experience in following smartly done before. In this case, both Teachers and Principals are constrained in the selection of such discerning participants. For that with the use of a computer-based information system can reduce the constraints in the selection of intelligent participants carefully. Decision support system is a computer-based system that can assist decision makers in generating decisions, by applying method methods, then the results are given on the DSS more effective and efficient